Indonesia Facing Challenges of Pharmaceutical Care Implementation in Community Pharmacies: A Legal Perspective - I Gusti Ayu Rai Widowati; Mohammad Zamroni (Magister of Law, Post Graduate Program, Universitas Warmadewa, 2023)
Pharmaceutical Care (PC) is a kind of interactive comprehensive service offered by the pharmacist to the patient, in which the pharmacist's physical presence is expected when providing pharmaceutical services to the patients at the pharmacy. However, pharmacists still prioritized internal management over interacting directly with patients. The objective of this research is to glance at the legal challenges of PC implementation in Indonesian community pharmacies. The normative juridical research method has been used, with a conceptual and legal approach. PC implementation in community pharmacies experiences major-level, mid-level, and minor-level challenges. PC standards in pharmacies are legally stated in Regulation of the Minister of Health of the Republic of Indonesia No. 73 of 2016, but there are still conflicts between pharmaceutical management and PC implementation. In the incident of a medication error, the pharmacist as the person responsible for PC in the pharmacy, is legally responsible. Pharmacists who do not meet PC standards in community pharmacies encounter administrative, civil, and criminal consequences.